Pengaruh Kualitas Layanan dan Tingkat Harga terhadap Loyalitas Pelanggan: (Studi pada AHASS 7662 Simongan Jaya Semarang) - Kurniawan, Muhammad Agung Wahyu; Novian, Mochamad Hangga (Prodi Administrasi Bisnis FISIP Universitas Tulang Bawang Lampung, 2024)
This study aims to determine and explain the effect of service quality and price level on customer loyalty at AHASS 7662 Simongan Jaya Semarang. The research was conducted by distributing questionnaires via googleform to 100 respondents and processed with the help of IBM SPSS version 26. The results showed that: (1) There is a positive and significant effect of service quality on customer loyalty with the value of tcount> ttable, namely 5.799> 1.984, (2) There is a positive and significant effect of price level on customer loyalty, the value of tcount> ttable, namely 10.124> 1.984, (3) There is a positive and significant effect of service quality and price level simultaneously on customer loyalty with the value of Fcount> Ftabel, namely 10.124> 3.09. Suggestions in this study are (1) Service providers are expected to complete the availability of motorbike or spearpat products so that customers can easily reach the services needed, (2) Service providers are expected to review and consider the price level given to customers with competitor price levels for similar services. Keywords: service quality, price level, customer loyalty